z-3z=6z-2-z

Simple and best practice solution for z-3z=6z-2-z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z-3z=6z-2-z equation:


Simplifying
z + -3z = 6z + -2 + -1z

Combine like terms: z + -3z = -2z
-2z = 6z + -2 + -1z

Reorder the terms:
-2z = -2 + 6z + -1z

Combine like terms: 6z + -1z = 5z
-2z = -2 + 5z

Solving
-2z = -2 + 5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-5z' to each side of the equation.
-2z + -5z = -2 + 5z + -5z

Combine like terms: -2z + -5z = -7z
-7z = -2 + 5z + -5z

Combine like terms: 5z + -5z = 0
-7z = -2 + 0
-7z = -2

Divide each side by '-7'.
z = 0.2857142857

Simplifying
z = 0.2857142857

See similar equations:

| 20n-30=20-5n | | 3/4x+1/6+1/2x+4/5 | | 0.12y+0.08(y+2000)=1160 | | 3(x-6)=14-x | | 64*19= | | 0.3x^2-1.8x+0.3=0 | | -2(4x-18)+3x=6 | | -3x+18=3x-18 | | 0.12=3h | | 17=x/2+15 | | 5+x/6=-8 | | X+(3/2)=(-3/5) | | [3x-5]+4=14 | | 1/7x-5=7 | | 9+x/3=27 | | y=x^3-3x^2-7x+33 | | 19*.20= | | 4(3+3x)-2=34 | | 4x-13+3x=2+7x-15 | | 10x^2-10x-1=0 | | 2(c-5)-2=8+c | | 9-9x-6-3x=6 | | 10-3(2x-7)=5x-24 | | -8.1-4z-6.6-z=-4z+12.9 | | 7n-21+3n+15=10 | | 39=3 | | -6Y+9(-6Y+6)=7+9(5-Y) | | x+x/2-16=135 | | 9(y-6)=8(8+y) | | -15b+15b=0 | | 20+9(4x-4)=10(2x-1) | | 3(5cx+y)=14cx-6yforx |

Equations solver categories